Dampak Pinjaman Online Terhadap Realisasi Proses Kredit Pemilikan Rumah FLPP Untuk Masyarakat Berpenghasilan Rendah - Iwan Hermawan (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2026)
The Housing Financing Liquidity Facility (FLPP) program aims to increase access to home ownership for Low-Income Communities (MBR). However, the realization of FLPP Home Ownership Loans (KPR) is influenced not only by the availability of financing and the readiness of the distributing bank, but also by the financial viability of prospective borrowers. One increasingly important factor is the history of online loans after the Information Technology-Based Joint Funding Service (LPBBTI) providers were integrated into the Financial Information Services System (SLIK) of the Financial Services Authority (OJK). This article aims to analyze the impact of online loans on the realization of FLPP mortgages through a literature review and policy analysis of OJK regulations, information from the Tapera Fund Management Agency (BP Tapera), and literature on credit information sharing and credit risk management. The analysis results show that online loans affect the FLPP mortgage process through the transparency of liability data in SLIK, collectibility assessments, repayment capacity, bank risk perception, and repayment status updates. The OJK's 2026 policy, which limits SLIK information to loans above IDR 1 million and accelerates repayment status updates to a maximum of three business days, has the potential to reduce administrative barriers for prospective borrowers. Nevertheless, the principle of bank prudence remains the primary basis for assessing creditworthiness.